Positive family history of cardiovascular disease and long-term outcomes after coronary artery bypass grafting: a genetic paradox?. (9th December 2019) - Ruttmann, Elfriede; Abfalterer, Hannes; Dietl, Marion; Wagner, Julian; Kilo, Juliane; Grimm, Michael; Bates, Katie; Fritz, Josef; Ulmer, Hanno
Abstract: OBJECTIVES: Parental cardiovascular disease (CVD) is a known risk factor for premature CVD. It is unknown whether a positive family history (PFH) affects outcomes after coronary artery bypass grafting (CABG). METHODS: Data come from a retrospective longitudinal study of CABG patients consecutively recruited from 2001 to 2018 ( n = 5389). From this study, 2535 patients with premature CVD undergoing CABG under the age of 60 years and information on parental CVD were identified. The Framingham offspring study criteria were used to identify PFH of CVD. Multivariable Cox proportional hazards regression models were used to assess the effect of PFH on overall and major adverse cardiovascular and cerebrovascular event-free survival. RESULTS: A total of 273 deaths and 428 major adverse cardiovascular and cerebrovascular events occurred during follow-up. PFH of CVD was found in 54.2% of patients ( n = 1375). Within these patients, 66.1% had a father who experienced a premature cardiovascular event ( n = 909), 27.8% a mother ( n = 382) and 6.1% both a mother and a father ( n = 84). In the majority of cases, the patient's parent had experienced a cardiac event (85.9%, n = 1181) and 14.1% of patients with PFH reported parental stroke ( n = 194). Following CABG, PFH was associated with improved overall [adjusted hazards ratio (HR) 0.67, 95% confidence interval (CI) 0.50–0.90; P = 0.008] and major adverse cardiovascular and cerebrovascular event-free survival (adjusted HR 0.73, 95% CI 0.68–0.89; P = 0.01). Among the covariates adjusted for age, diabetes, renal insufficiency, peripheral arterial disease, ejection fraction, previous cerebrovascular events and previous mediastinal radiation were all associated with poorer outcomes. CONCLUSIONS: Although it is well established that a PFH increases the risk of requiring CABG at younger ages, this study shows that, paradoxically, PFH is also protective regarding long-term outcomes. Registration number local IRB: UN4232 297/4.3 (retrospective study).